Climate-Driven Risks in Tuna Fishing in Indonesia: A Financial Distress Likelihood - Wibowo, Martino; Rekarti, Endi; Anwar, Kasful; Indarwati, Tias Andarini; Aumeboonsuke, Vesarach (Jakarta Technical University of Fisheries, 2024)
The purpose of this research is to investigate how climate change is influencing the risks within the tuna fishing sector in Indonesia. Changes in the environment, like increasing sea temperatures and shifting ocean currents, have impacted the movement and migration patterns of tuna, directly impacting the industry sustainability. The significance of this study lies in the pressing necessity to comprehend the ways in which climate change is impacting the risks encountered by businesses operating in the tuna fishing industry. This research aims to assess the risks that tuna fishing businesses encounter as a result of climate change and to determine how they affect the company's stock value. To conduct this research, a panel data evaluation approach was employed using seven publicly traded companies engaged in the tuna industry as sample subjects. The data used was sourced from company filings with the Indonesia Stock Exchange and capital market figures from the Financial Services Authority (OJK). The research utilizes an Altman Z Score model to evaluate the financial health and risk of bankruptcy of a company by incorporating dummy variables associated with increasing sea temperatures into its analysis. This study aims to offer policymakers evidence-based guidance regarding the consequences of different management strategies for addressing climate fluctuations. Furthermore, the research underscores the significance of taking factors into account when managing financial risks, especially in ensuring the long-term viability of the tuna fishing sector. The uniqueness of this study is found in its approach of merging financial risk analysis with risk assessment methods by utilizing a model that integrates both biological and economic elements to offer a holistic framework for decision-making within the sustainable fisheries sector.